Environmental evolution in the Picos de Europa (Cantabrian Mountains, SW Europe) since the Last Glaciation. (15th April 2016) - Ruiz-Fernández, Jesús; Oliva, Marc; Cruces, Anabela; Lopes, Vera; Freitas, Maria da Conceição; Andrade, César; García-Hernández, Cristina; López-Sáez, José Antonio; Geraldes, Miguel
Abstract: The Western Massif of the Picos de Europa (latitude 43° N, longitude 4–5° W) includes some of the highest peaks in the Cantabrian Mountains. This massif was heavily glaciated during the Last Glaciation, though the post-glacial environmental evolution is still poorly understood. Using a complementary geomorphological and sedimentological approach, we have reconstructed the environmental events occurred in this massif since the last Pleistocene glaciation. The geomorphological distribution of glacial landforms suggests the occurrence of four main glacial stages: maximum glacial advance, glacial expansion after the maximum advance, Late Glacial and Little Ice Age. Moreover, a 5.4-m long sedimentary sequence was retrieved from the karstic depression of Belbín providing a continuous record of the paleoenvironmental conditions in this area since the Last Glaciation until nowadays. This section suggests that the maximum glacial expansion occurred at a minimum age of 37.2 ka cal BP, significantly prior to the global Last Glacial Maximum. Subsequently, periglacial processes prevailed in the mid lands of the massif until glaciers expanded between 22.5 and 18.7 ka cal BP. Following the melting of the glaciers, a shallow lake appeared in the Belbín depression. Lake sediments do not show evidence of a cold stage during the Late Glacial, when moraine systems formed at higher locations. The terrestrification of this lake started at 8 ka cal BP and the area turned into grassland. At 4.9 ka cal BP the existence of charcoal particles in the sediments of Belbín sequence reveals the onset of human occupation in the massif through the use of fire activity for grazing purposes. Finally, the presence of moraines inside the highest northern cirques shows evidence of the last glacial phase that occurred during the Little Ice Age cold event. Since then, the warming climate has led to the melting of these glaciers and periglacial processes prevail in the high lands of the massif. Highlights: We reconstructed past environments in Picos de Europa since the Last Glaciation. The maximum expansion of glaciers occurred at a minimum age of 37.2 ka cal BP. Four glacial stages: maximum advance, second maximum advance, Late Glacial and LIA. These stages were parallel to environmental changes (periglacial, lake, peatland). Fire activity started at 4.9 ka cal BP, onset of human impact in the high lands.